Offshore floating vertical axis wind turbines, dynamics modelling state of the art. Part II: Mooring line and structural dynamics - Borg, Michael; Collu, Maurizio; Kolios, Athanasios (Elsevier, 2014)
The need to exploit enhanced wind resources far offshore as well as in deep waters requires the use of floating support structures to become economically viable. The conventional three-bladed horizontal axis wind turbine may not continue to be the optimal design for floating applications. Therefore it is important to assess alternative concepts in this context that may be more suitable. Vertical axis wind turbines (VAWTs) are a promising concept, and it is important to first understand the coupled and relatively complex dynamics of floating VAWTs to assess their technical feasibility. As part of this task, a series of articles have been developed to present a comprehensive literature review covering the various areas of engineering expertise required to understand the coupled dynamics involved in floating VAWTs. This second article focuses on the modelling of mooring systems and structural behaviour of floating VAWTs, discussing various mathematical models and their suitability within the context of developing a model of coupled dynamics for. Emphasis is placed on computational aspects of model selection and development as computational efficiency is an important aspect during preliminary design stages. This paper has been written both for researchers new to this research area, outlining underlying theory whilst providing a comprehensive review of the latest work, and for experts in this area, providing a comprehensive list of the relevant references where the details of modelling approaches may be found.
Keywords: floating offshore wind turbines; vertical axis wind turbine; VAWT; coupled dynamics; mooring; structural dynamics